Recombinant Tissue Factor Pathway Inhibitor Enhances the Binding of Factor Xa to Human Monocytes - Li, Anguo; Chang, Alvin C.K.; Peer, Glenn T.; Wun, Tze-Chen; Taylor, Fletcher B., Jr. (Thrombosis and Haemostasis, 2001)
Tissue factor pathway inhibitor (TFPI) is a kunitz-type inhibitor of activated factor X (Xa). TFPI was reported to mediate Xa binding to a few of carcinoma cell lines. In this study it was observed that the Xa activity associated with human peripheral blood mononuclear cells (PBMC) incubated with Xa in the presence of recombinant TFPI (rTFPI) was much higher than with Xa alone. Xa activity on PBMC was also observed after whole blood was incubated with pre-formed Xa/TFPI complex. Further studies with flow cytometric analysis demonstrate that rTFPI enhances the binding of Xa to human monocytes. Western blot analysis showed that rTFPI was cleaved into a few of fragments after its incubation with monocytes either in the presence or absence of Xa. Based on these results and the observations reported by others, we speculate that Xa/TFPI complex may bind to human monocytes by a yet unidentified mechanism. The recovery of Xa activity from Xa/TFPI complex on PBMC may be related to the cleavage of rTFPI by Xa and/or monocyte proteases. This observation suggests a new mechanism by which monocytes become procoagulant in some pathological conditions in addition of the well known tissue factor expression on proinflammatic monocytes.
Keywords: TFPI; factor X (Xa); rTFPI